COMPARISON OF TOLL LIKE RECEPTOR 2 AND 4 MACROPHAGE EXPRESSION CAUSED BY NEEM LEAVES AQUEOES EXTRACT IN ORAL CAVITY: PERBANDINGAN TOLL-LIKE RECEPTOR 2 DAN 4 ESKPRESI MAKROFAG CAIRAN EKSTRAK DAUN NEEM DALAM RONGGA MULUT - I Dewa Ayu Ratna Dewanti, (Dentika: Dental Journal, 2010)
Neem is one of the traditional medicine trees known by society and has function as immunomodulatory. TLR2 and TLR4 played an important role in recognition of infection. This experimental study aimed to know the comparison of TLR2 with TLR4 macrophage expression of Aqueous extract from neem (Azadirachta indica) leaves in oral cavity. The subjects of this research were 24 male-wistar rats divided into five groups: Control Group (ko) had no treatment. Group II was fed with 50 mg/day/kg body weigth aqueous extracts from neem leaves (KP1), group III was fed with 100 meÂ¢/day/kg body weigth aqueous extract from neem leaves (KP2), group IV was fed with 200 mg/day/kg body weigth aqueous extract from neem leaves (KP3). After 21 days, rats would be killed and cut there tongues and analized by imunohistochemy. Data obtained will be analyzed using Anova and followed by HSD and linier regression. The result showed that there was no significant different (p<0,05) between comparison of TLR2 with TLR4 macrophage expression of experimental groups V. There was significant difference in the increasing of TLR2 and TLR4 between KO with KP. As conclusion. there was increasing of TLR2 and TLR4 macrophage expression of aqueous extract {rom neem leaves in oral cavity, but there was no significant difference.